Women and the autobiographical impulse a history - Caine, Barbara 1948- (Bloomsbury Academic, 2023)
"Esteemed historian Barbara Caine skilfully produces an overview of British women's autobiographies over three centuries, showing important changes in motivation, context, style, and life experiences"--
Keywords: Schriftstellerin; Autobiografische Literatur; Englisch; Autobiography / Women authors; Women / England / Biography / History and criticism; England / Biography / History and criticism; Écrits de femmes autobiographiques; Femmes / Angleterre / Biographies / Histoire et critique; Angleterre / Biographies / Histoire et critique; Biography; Women / Biography; England; Criticism, interpretation, etc